2015
DOI: 10.1121/1.4929731
|View full text |Cite
|
Sign up to set email alerts
|

Toddlers' comprehension of degraded signals: Noise-vocoded versus sine-wave analogs

Abstract: Recent findings suggest that development changes the ability to comprehend degraded speech. Preschool children showed greater difficulties perceiving noise-vocoded speech (a signal that integrates amplitude over broad frequency bands) than sine-wave speech (which maintains the spectral peaks without the spectrum envelope). In contrast, 27-month-old children in the present study could recognize speech with either type of degradation and performed slightly better with eight-channel vocoded speech than with sine-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 14 publications
0
10
0
Order By: Relevance
“…Studies in NH pre-school children and toddlers suggest that the ability to process spectrally sparse speech (sinewave speech or NBV speech with 8 channels) is in place at early stages of development (Nittrouer et al, 2009, Newman & Chatterjee, 2013; Newman et al, 2015). However, Newman & Chatterjee (2013) and Newman et al (2015) also suggest that the performance of young children in such tasks depends strongly on the degree of spectral resolution. This is consistent with findings of Eisenberg et al (2000).…”
Section: Discussionmentioning
confidence: 99%
“…Studies in NH pre-school children and toddlers suggest that the ability to process spectrally sparse speech (sinewave speech or NBV speech with 8 channels) is in place at early stages of development (Nittrouer et al, 2009, Newman & Chatterjee, 2013; Newman et al, 2015). However, Newman & Chatterjee (2013) and Newman et al (2015) also suggest that the performance of young children in such tasks depends strongly on the degree of spectral resolution. This is consistent with findings of Eisenberg et al (2000).…”
Section: Discussionmentioning
confidence: 99%
“…To date, vocoder studies with cNH have primarily focused on the number of spectral channels needed to achieve high levels of speech perception. Like adults, vocoded speech perception performance of cNH improves as the number of channels increases (Eisenberg et al 2000;Dorman et al 2000;Nittrouer and Lowenstein 2009;Nittrouer et al 2010;Newman and Chatterjee 2013;Warner-Czyz et al 2014;Newman et al 2015). Perhaps more importantly, however, these investigations have shown that the ability to recognize spectrally degraded speech improves with age for cNH, and that young children require more channels than older children and adults to achieve asymptotic speech perception performance (Dorman et al 2000;Eisenberg et al 2000Eisenberg et al , 2002Vongpaisal et al 2012;Roman et al 2017).…”
Section: Introductionmentioning
confidence: 97%
“…Towards the older end of the lifespan, hearing loss and/or advancing age decreases vocoded speech recognition [8,14,22,23]. Towards the younger end of the lifespan, vocoded speech recognition performance is often poorer for children compared to adults [12,13,[24][25][26][27][28][29]. Studying vocoded speech recognition in children is important as it helps clarify how language is processed and learned via highly degraded signals as are presented via a CI.…”
Section: Introductionmentioning
confidence: 99%